IICA strategy for Trinidad and Tobago : 2014-2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The IICA country strategy (ICS) for Trinidad and Tobago outlines a comprehensive plan of action for addressing the needs or demands of the many stakeholders along the agrifood sector. The strategies are constructed within the general framework of the IICA’s Medium Term Plan (MTP) 2014-2018. In essence, the ICS reflects the Institute’s Inter-thematic and Multi-level work which the IICA Office in Trinidad and Tobago will be undertaking during the period 2014-2018. Operationally, the ICS defines areas that IICA will be concentrating its efforts and capabilities in addressing the demands and needs of stakeholders in the sector. Four (4) instruments of Technical Corporation will be used for implementing the national technical corporation programme for addressing the needs and demands of Trinidad and Tobago in the areas of agriculture and food and nutrition security. These instruments include four (4) Flagship Projects; projects financed with External Resources; Rapid Response Actions and the Technical Cooperation Fund.